(untitled) (Research, Society and Development, 2024)
The main objective of this theme is to understand and analyze the importance of the role of the nurse in the guidance and care of children and adolescent victims of sexual violence. It also seeks to identify the main difficulties and challenges faced in job by nursing professionals in this context, and the best practices for victims’ prevention, identification, and care. Methodology: Qualitative research: Interviews with nursing professionals, victims of sexual violence, and their families, to understand the experiences and perceptions about the Theme. Application of questionnaires for a sample of nursing professionals, to evaluate knowledge and questions related to public care for victims of sexual violence. Consideration: The nurse plays a fundamental role in the prevention, identification, and care of these cases, acting as a trusted professional and offering comprehensive care to victims and their families. Nursing professionals must be trained to act effectively in the prevention and care of victims of sexual violence, acquiring knowledge about legislation, the psychological and social aspects of violence, and communication and reception techniques. Conclusion: Through this research and actions, it is possible to strengthen the role of the nurse work in the prevention and care of these victims, contributing to the construction of a fairer and safer society.